Key Drivers of Energy Consumption in the Gulf Cooperation Council Countries: A Panel Analysis - Chaabouni, Ines; Abid, Ihsen (Engineering, Technology & Applied Science Research, 2025)
The objective of this study is to examine the factors that influence energy consumption, a critical component of both industrial and everyday life that is projected to increase annually. The research focuses on Gulf Cooperation Council (GCC) countries and uses panel data from 1990 to 2023 to assess the impact of economic growth, trade openness, population growth, urbanization, inflation, and Foreign Direct Investments (FDI) on energy consumption. The findings, derived from a rigorous Augmented Mean Group (AMG) regression analysis, reveal a positive and significant relationship between economic growth, trade openness, and inflation on energy consumption. However, the study also outlines that FDI, population growth, and urbanization do not exert a significant influence on energy use. The analysis highlights a critical challenge faced by GCC countries: the need to balance high industrial energy consumption with sustainability goals. The study underscores the necessity of transitioning to sustainable practices, including energy efficiency and renewable energy adoption, as crucial elements for achieving long-term growth and climate commitments. This research contributes to the ongoing discourse on sustainable development in the region and underscores the necessity of incorporating environmental factors into economic growth strategies.